DEGRADASI BEBERAPA SIFAT FISIK TANAH AKIBAT ALIH GUNA LAHAN HUTAN MENJADI LAHAN PERKEBUNAN KAKAO (Theobroma cacao L.) DI DESA SEJAHTERA, PALOLO - Datukramat, Rahma Sari; Monde, Anton; Paloloang, Abd Kadir (AGROTEKBIS, 2013)
Research has been conducted to determine some physical soilproperties degradation due to land use change of forest land into plantations of cacao ( Theobroma cacao L. ) in Sejahtera village. The method used in this study was using the survey method. The observations and soil sampling location determined by purposive sampling technique such as observation and soil sampling location determined based on the researchers consideration on soil conditions, slope, land use domination and the age of cocoa contained in the study area. The results shown that there has been a decrease in land capacity because of land use change of forest into cocoa plantations, which forest land has physical characteristics of the soil with a sandy loam texture , permeability classified as moderate , high bulk density, saturated soil water content is quite good, as well as relatively good porosity, whereas cocoa land has physical characteristics with sandy clay loam texture, relatively little slow permeability, high bulk density, saturated soil water content is quite good, as well as the relatively poor porosity.